Protective effect of Ipomoea aquatica against reserpine induced oxidative stress in brain using mice - Dwivedi, Gaurav; Tomar, Vivek (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The aim of the present study was to investigate the protective potential of alcoholic extract of Ipomoea aquatica extract against haloperidol induced catatonia, reserpine induced hypokinesia and reserpine induced oxidative stress. Methods: The mice were treated with reserpine for three days every other day. It was observed that Ipomoea aquatica MA extract significantly decreased haloperidol induced catatonia at 30, 60, 90 and 120 minutes respectively. The biochemical analysis of brain showed that the treatment with reserpine significantly enhanced peroxidation of lipid and lower levels of superoxide dismutase (SOD), catalase (CAT) and glutathione reductase (GSH), which will be an index for oxidative stress process. Co-administration of extract at (200 mg/kg and 400 mg/kg) significantly lowered the lipid peroxidation and reversed the decrease in brain SOD, CAT and GSH levels. Results: It was observed that the alcoholic extract of Ipomoea aquatica had a protective role against haloperidol induced catatonia, reserpine induced hypokinesia, and reserpine induced oxidative stress. Conclusions: Ipomoea aquatica showed significant activity at the dose of (400 mg/kg).